2023
DOI: 10.36103/ijas.v54i1.1678
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Evaluation of Bioactive Compounds in Soybean

Abstract: This study was aimed to estimate the antioxidants, antibacterial, and antifungal activities of methanolic extract from soybean seeds against pathogenic microorganisms. The methanolic extract was prepared from defatted soybean flour. Total phenolics content (TPC), total flavonoid content (TFC), and the major phenolic, flavonoid, and isoflavone compounds in soybean extract were estimated by HPLC. On the other hand, biological activities such as antioxidants, antibacterial, and antifungal activities were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…C. albicans and T. rubrum are affected by daidzein and genistein. Glycitein shows effective antifungal as well as antibacterial properties [ 89 , 90 ]. In experiments using antimicrobial agents, strains susceptible to resveratrol (50 µg/mL) and curcumin (20 µg/mL) show sub-MIC levels lowering evaluated virulence factors by at least 50% (IC 50 ).…”
Section: Activities As Antimicrobial Agents Of Several Polyphenolsmentioning
confidence: 99%
“…C. albicans and T. rubrum are affected by daidzein and genistein. Glycitein shows effective antifungal as well as antibacterial properties [ 89 , 90 ]. In experiments using antimicrobial agents, strains susceptible to resveratrol (50 µg/mL) and curcumin (20 µg/mL) show sub-MIC levels lowering evaluated virulence factors by at least 50% (IC 50 ).…”
Section: Activities As Antimicrobial Agents Of Several Polyphenolsmentioning
confidence: 99%
“…Surface conditioning is vital for cell growth, and often creates a favorable environment for bacterial growth, and enhances adhesion. Cells attach to surfaces, leading to infection [29]. Therefore, it can be assumed that the presence of the plant extract in the growth medium led to an unfavorable condition that could prevent cell attachment or reduce surface adhesion.…”
Section: Total Bacterial Count During the Period Of Cold Storage Of T...mentioning
confidence: 99%
“…Many plant secondary metabolite compounds have characterized antibacterial activities against plant pathogens, which can be effectively applied to fight human pathogens. Moreover, the antibacterial activities of many metabolites are used differently from conventional drugs and can therefore be important in enhancing antibacterial therapy [3,29] also found that flavonoids should be found as effective antimicrobial agents against a wide range of pathogenic microorganisms in vitro.…”
Section: Total Bacterial Count During the Period Of Cold Storage Of T...mentioning
confidence: 99%